STOP COVID-19 CA: Community engagement to address the disparate impacts of the COVID-19 pandemic in California - Casillas, Alejandra; Rosas, Lisa G.; Carson, Savanna L.; Orechwa, Allison; North, Gemma; AuYoung, Mona; Kim, Gloria; Guereca, Jesus A.; Ramers, Christian B.; Burke, Nancy J.; Corchado, Claudia G.; Aguilar-Gaxiola, Sergio; et al. (Frontiers in Health Services, 2022)
Objective To describe the early activities and lessons of the Share, Trust, Organize, Partner COVID-19 California Alliance (STOP COVID-19 CA), the California awardee of the NIH-funded multi-state Community Engagement Alliance (CEAL) against COVID-19. The Alliance was established to ensure equity in Coronavirus-19 disease (COVID-19) research, clinical practice, and public health for communities most impacted by the COVID-19 pandemic. Study setting The STOP COVID-19 CA Alliance network of 11 universities and affiliated partner community-based organizations (CBOs) across California. Study design Mixed methods evaluation consisting of an analysis of activity (August 2020 to December 2021) detailed in reports submitted by community-academic teams and a survey (August 2021) of academic investigators and affiliated community-based organization (CBO) partners. Data collection We summarized activities from the 11 community-academic teams' progress reports and described results from an online survey of academic investigators and CBO partners in the California Alliance. Principal findings A review of progress reports (n = 256) showed that teams fielded surveys to 11,000 Californians, conducted 133 focus groups, partnered with 29 vaccine/therapeutics clinical trials, and led more than 300 town halls and vaccine events that reached Californians from communities disproportionately impacted by COVID-19. Survey responses from academic investigators and CBO partners emphasized the importance of learning from the successes and challenges of the California Alliance teams' COVID-19 initiatives. Both academic and CBO respondents highlighted the need for streamlined federal and institutional administrative policies, and fiscal practices to promote more effective and timely operations of teams in their efforts to address the numerous underlying health and social disparities that predispose their communities to higher rates of, and poor outcomes from, COVID-19. Conclusions STOP COVID-19 CA represents a new and potentially sustainable statewide community engagement model for addressing health disparities in multiethnic/multicultural and geographically dispersed communities.